2012
DOI: 10.4102/sajhivmed.v13i2.146
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of blood and blood products in HIV-infected patients

Abstract: Despite numerous publications on the appropriate use of blood and blood products, few specifically consider the role of transfusion in the management of HIV. This review is a synthesis of conditions encountered in the management of HIV-infected patients where the transfusion of blood or blood products may be indicated. A consistent message emerging from the review is that the principles of transfusion medicine do not differ between HIV-negative and -positive patients. The aim of the review is to provide clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…The indication of transfusing patients infected with HIV/AIDS does not differ substantially compared with HIV-negative [25]. However, the main immunohematological problem is the positivity of pretransfusional crossmatch test (Figure 3) [10,26].…”
Section: Selection Of Blood To Be Transfusedmentioning
confidence: 99%
“…The indication of transfusing patients infected with HIV/AIDS does not differ substantially compared with HIV-negative [25]. However, the main immunohematological problem is the positivity of pretransfusional crossmatch test (Figure 3) [10,26].…”
Section: Selection Of Blood To Be Transfusedmentioning
confidence: 99%
“…[7] Additionally, Alli et al [1] propose that a blood film be done on all patients, but provide no evidence to support the diagnostic yield of this approach. In their algorithm for investigation of anaemia in HIV infection in southern Africa, Van den Berg et al [8] do not advocate a blood film as routine. Nairz et al [9] suggest that a blood film would be indicated primarily to diagnose conditions where there is an increased reticulocyte production index (RPI) or macrocytosis with a low RPI.…”
Section: An Approach To Anaemia Diagnosisconcerns In Primary Carementioning
confidence: 99%
“…[14,15] A third approach is to combine biochemical testing (ferritin, vitamin B 12 and folate) with morphological red blood cell indices for all patients. [8] There is no clarity on which approach is best in primary care. The third approach may be preferred in South Africa (SA), where nutrient deficiencies are common in females of reproductive age, e.g.…”
Section: An Approach To Anaemia Diagnosisconcerns In Primary Carementioning
confidence: 99%
“…HIV-related anemia is associated with fatigue, decreased quality of life [ 7 ], and a greatly increased mortality risk [ 8 – 11 ]. Although the South African HIV Clinician's Society has published recommendations on the management of anemia and blood transfusions among patients infected with HIV, there are no normative international guidelines for the management of HIV-related anemia in sub-Saharan Africa or other resource-limited settings [ 12 ].…”
mentioning
confidence: 99%
“…In addition, some evidence suggests that blood transfusions are associated with modest increases in plasma HIV-1 RNA levels and increased mortality risk [ 11 , 18 20 ]. This has led some clinicians to conclude that transfusions should be used sparingly among patients infected with HIV [ 12 ]. The limited evidence to date to support such caution is derived exclusively from North America, and thus this issue has not yet been investigated in sub-Saharan Africa, where the prevalence of HIV-related anemia remains high.…”
mentioning
confidence: 99%